Socialinis teisingumas XXI amžiuje: ar gerovės valstybė vis dar prasminga teorinė konstrukcija šiuolaikinei demokratijai? - Valantiejus, Vaidotas (Sociologija. Mintis ir veiksmas, 2023)
The article examines the ideologem of the decline of the welfare state. The main question is whether the welfare state is still possible in contemporary society. It is argued that the thesis of the impossibility of the welfare state is an ideological statement, and the supposedly objective demise of the welfare state is what M. Foucault called ‘the regime of truth’. The article contrasts the procedural and substantive features of the concept of the welfare state. According to J. Habermas’ theory of legitimation crisis, the welfare state and the social rights it provides are not treated as paternalistic and freedom-restricting measures but rather as the foundation of legitimation.
Keywords: gerovės valstybė; ideologija; legitimacija; socialinės teisės